Semiotic Analysis of Twitter Logo Change to Logo X: User Interface (UI) Design and User Psychological Perspectives - Yulianto, Arief; Putri, I Gusti Ayu Agung Aristi (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The development of a logo has become a visual identity for big brands. Some brands create logos to be the biggest promotional resource to attract the mindset of their customers. In the context of technology applications, a logo is not just a symbol, but also an integral part of the User Interface (UI) that influences user interaction and engagement. Twitter, as one of the largest social media platforms in the world, has undergone a significant change in its visual identity by replacing its iconic logo to a new logo known as X. This research uses a descriptive analysis research method with comparative analysis from the researcher himself and data approaches carried out with the 5W + 1H theory. Semiotic Theory using Roland Barthes theory which explains that the first stage of signification is the relationship of signifier (expression) and signified (content) in a sign to external reality. In addition, this analysis also looks at the UI Design side and the user psychology side with the Gestalt Psycholgy theory. The results and findings viewed in the context of UI design, these changes present new challenges and opportunities to create a consistent and engaging user experience. Users' psychological reactions were mixed, indicating that the logo change had a major impact on users' perception and engagement with the app. Through the 5W+1H concept and personal analysis, this research provides a comprehensive understanding of the meaning and impact of the logo change.